2007
DOI: 10.2190/8ptl-p745-58u1-3330
|View full text |Cite
|
Sign up to set email alerts
|

Women of the 1950s and the “Normative” Life Course: The Implications of Childlessness, Fertility Timing, and Marital Status for Psychological Well-Being in Late Midlife

Abstract: We explore women's psychological well-being in late midlife in relation to childlessness and timing of entry into motherhood. Using two U.S. surveys, Health and Retirement Study (HRS) (1992) and National Survey of Families and Households (NSFH) (Sweet, Bumpass, & Call, 1988), we assess the well-being of childless women in their 50s compared to mothers with early, delayed, or normatively timed first births. We focus on the cohorts born between 1928 and 1941, who experienced strong normative pressures during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 61 publications
5
97
2
1
Order By: Relevance
“…For example, young parents show higher levels of distress than non-parents (Cleary and Mechanic 1983;Gore and Mangione 1983;Lovell-Troy 1983;Margolis and Myrskyla 2011;McLanahan and Adams 1987). At older ages, there is no difference in well-being by parental status (Connidis and McMullin 1993;Koropeckyj-Cox et al 2007;Rempel 1985;Ross and Huber 1985), or parents have even higher levels of well-being than the childless (Margolis and Myrskyla 2011). These cross-sectional analyses provide important insights into the fertility-happiness association, but have limited power in informing us about causal relationships.…”
Section: Trajectories Of Parental Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, young parents show higher levels of distress than non-parents (Cleary and Mechanic 1983;Gore and Mangione 1983;Lovell-Troy 1983;Margolis and Myrskyla 2011;McLanahan and Adams 1987). At older ages, there is no difference in well-being by parental status (Connidis and McMullin 1993;Koropeckyj-Cox et al 2007;Rempel 1985;Ross and Huber 1985), or parents have even higher levels of well-being than the childless (Margolis and Myrskyla 2011). These cross-sectional analyses provide important insights into the fertility-happiness association, but have limited power in informing us about causal relationships.…”
Section: Trajectories Of Parental Well-beingmentioning
confidence: 99%
“…Such comparisons, which are plentiful in the literature (Aassve et al 2009;Billari 2009;Koropeckyj et al 2007;Margolis and Myrskyla 2011), suffer from the potential bias caused by unobserved confounders such as personality and other fixed factors which may be associated with both happiness and childbearing behavior. 7 Our strategy allows controlling for such factors.…”
Section: Empirical Approachmentioning
confidence: 99%
“…An early age at entry to parenthood and large family size (high parity) may lead to socioeconomic strain and limit opportunities for career involvement and progression, especially for women, which is relevant as occupational complexity is associated with later life cognition (Andel et al, 2014). Additionally "off-time" fertility may increase risks of depression and a poorer sense of control in life, partly due to associations with socioeconomic factors and possibly because of the reduced resilience of young parents to the stresses involved in raising children (Evenson & Simon, 2005;Koropeckyj-Cox, Pienta, & Brown, 2007;. The timing of parenthood, and to some extent number of children, is socially patterned and strongly associated with levels of education.…”
Section: Parenthood Social Relations and Cognitive Functionmentioning
confidence: 99%
“…For instance, young parents tend to report higher levels of distress than young non-parents (Cleary and Mechanic 1983;Gore and Mangione 1983;Lovell-Troy 1983;Margolis and Myrskylä 2011;McLanahan and Adams 1987). Studies have found that, at older ages, there is either no difference between childless adults and parents in terms of LS (Connidis and McMullin 1993;Koropeckyj-Cox et al 2007;Rempel 1985), or that parents display higher levels of well-being than their childless counterparts (Margolis and Myrskylä 2011). Given the general objective of our study, however, we did not confine the analysis to a specific age group.…”
Section: Model Specificationmentioning
confidence: 94%